Simultaneous Analysis of Sexual Stimulants and Anabolic Steroids as Adulterants in Dietary Supplements by High Performance Liquid Chromatography with Photodiode Array Detection - Viana, Carine; Marcon, Gabriela Z.; Dal Molin, Thais Ramos; Bohrer, Denise; do Nascimento, Paulo Cícero; de Carvalho, Leandro M. (Current Pharmaceutical Analysis, 2021)
Background: The illegal virtual market for food supplements facilitates fraud and adulteration. Worldwide concern for consumer safety is growing on the part regulatory agencies, healthcare professionals and consumers. Objective: This work aimed to evaluate the presence of sexual stimulants and anabolic steroids commonly used in the adulteration of dietary supplements through the development of a high performance liquid chromatography with the photodiode array detection (HPLC-DAD) method for the identification and quantification of these compounds. Methods: The mobile phase composed of an ammonium acetate solution, acetonitrile and methanol led to the efficient separation of vardenafil, testosterone base, testosterone propionate, tadalafil, sildenafil and yohimbine. Results: The assay was linear (r2> 0.999), precise (RSD% <0.5), accurate (99.1 to 105.2%), and the limits of detection and quantification were less than 0.05 and 0.15 μg/mL, respectively. Four samples of dietary supplements contained testosterone (n=1), tadalafil (n=2) and yohimbine (n=1) as adulterants. The adulterants found were in subtherapeutic doses, probably to reduce possible adverse effects and the action expected to appear natural. Since about 80% of adverse drug reactions are dose dependent, unpredictable adverse drug reactions are dose independent and based on idiosyncratic or allergic mechanisms or intolerance. Conclusion: The developed method is convenient and easily applicable for adulteration detection of the analyzed drugs in the multicomponent supplements.
Keywords: dysfunction